The Case for Public Financing of Environmental Common Goods for Health - Selina Lo; Sylvestre Gaudin; Carlos Corvalan; Alexandra J. Earle; Odd Hanssen; Annette Prüss-Ustun; Maria Neira; Agnès Soucat (Health Systems & Reform, 2019)
Safeguarding the continued existence of humanity requires building societies that cause minimal disruptions of the essential planetary systems that support life. While major successes have been achieved in improving health in recent decades, threats from the environment may undermine these gains, particularly among vulnerable populations and communities. In this article, we review the rationale for governments to invest in environmental Common Goods for Health (CGH) and identify functions that qualify as such, including interventions to improve air quality, develop sustainable food systems, preserve biodiversity, reduce greenhouse gas emissions, and encourage carbon sinks. Exploratory empirical analyses reveal that public spending on environmental goods does not crowd out public spending on health. Additionally, we find that improved governance is associated with better performance in environmental health outcomes, while the degrees of people’s participation in the political system together with voice and accountability are positively associated with performance in ambient air quality and biodiversity/habitat. We provide a list of functions that should be prioritized by governments across different sectors, and present preliminary costing of environmental CGH. As shown by the costing estimates presented here, these actions need not be especially expensive. Indeed, they are potentially cost-saving. The paper concludes with case examples of national governments that have successfully prioritized and financed environmental CGH. Because societal preferences may vary across time, government leaders seeking to protect the health of future generations must look beyond electoral cycles to enact policies that protect the environment and finance environmental CGH.